Speedflirt for Blackberry and Symbian, a study of across-platform application development method andits effects on user experience - Wang, Lei (My University, 2015)
The main purpose of this Master Thesis is to investigate how the mobile user experience of a mobile application is affected when the application is ported from platform to another platforms, and Framework guidelines which should be considered. The Speedflirt mobile application would be applied as a practical test for this research. The Mobile Life Ltd is an intelligent mobile application development professional company, and it was established in Singapore in 2006. The Mobile Life Ltd Ran their first office in Stockholm in 2009, and due to the increase of using intelligent mobile devices, mobile applications constitutes a large party of the project proposals received by the company. One of these projects is Speedflirt which is a location based mobile dating application. It is supported and cooperated among The Mobile Life Ltd, Speedflirt Pte Ltd and Metro (the metropolitan newspaper). The final output of my research should be a Speedflirt application which could is runnable on the Blackberry AppWord and Nokia OviStore; furthermore the framework guidelines would be considered for user experience during research.
Keywords: Data- och informationsvetenskap; Computer and Information Science